Sequential Weed Control Programs in Liberty Link Soybeans - D. E. Peterson; C. Thompson; C. L. Minihan (Kansas Agricultural Experiment Station Research Reports, 2017)
The development of glyphosate-resistant weeds has greatly complicated weed control in soybeans. Liberty Link soybeans provide growers an alternative herbicide option for postemergence weed control in soybeans. Liberty Link programs can provide effective weed control in a sequential weed-control program that includes effective preemergence residual herbicides at planting time followed by timely applications of Liberty.
Keywords: Liberty Link soybeans; henbit; giant ragweed; Palmer amaranth; large crabgrass